Essays on the Philosophy of George Berkeley
XIV, 273 p.
Keywords: A tercentenary conference of March, 1985, drew to Newport, Rhode Island, nearly all the most distinguished Berkeley scholars now active. The conference was organized by the International Berkeley Society, with the support of several institutions and many people (whose help is acknowl edged below). This volume represents a selection of the lead papers deliv ered at that conference, most now revised. The Cartesian marriage of Mind and Body has proved an uneasy union. Each side has claimed supremacy and usurped the rights of the other. In anglophone philosophy Body has lately had it all pretty much its own way, most dramatically in the Disappearance Theory of Mind, whose varieties vary in appeal and sophistication, but uniformly shock sensibili ties. Only recently has Mind reasserted itself, yet the voices of support are already a swelling chorus. "Welcome," Berkeley would respond, since " ... all the choir of heaven and furniture of the earth ... have not a subsis tence without a mind ... " (Principles, sect. 6). In fairness, Berkeley does playa Disappearance trick of his own - with Matter now into the hat. But his act is far subtler than any brute denial of the obvious, and seeks rather to explain than bluntly to reject. Perhaps we are today better prepared to appreciate his insights.